KOMUNIKASI INTERPERSONAL ORANGTUA DAN ANAK DENGAN PERILAKU BULLYING PADA SISWA SMPN 3 CANDI - Nourma Dwi Lestari; Ghozali Rusyid Affandi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
This research is motivated by the problem of bullying among students of SMPN 3 Candi. Many students like to engage in verbal and non-verbal bullying such as hitting their friends' heads and taunting them using animal names. The purpose of this study is to determine the relationship between parent-child interpersonal communication and bullying behavior. This research method is quantitative with a population of 842 students of SMPN 3 Candi and a sample of 247 students based on the Isaac & Michael table with a 5% error rate. The sample determination uses a proportionate stratified random sampling technique to determine the number of samples in each class because the population in this study is not homogeneous and proportionally stratified. The variables in this study are parent-child interpersonal communication and bullying behavior variables. Data collection in this study uses two psychological scales of Likert scale models adopted from previous studies. The hypothesis in this study is that there is a negative relationship between parent-child interpersonal communication and bullying behavior. Data analysis in this study uses the Pearson product moment correlation statistical test with the help of SPSS 26.0 for Windows. The results of the study showed that there was a negative relationship between interpersonal communication between parents and children and bullying behavior at SMPN 3 Candi with a value of r = -0.395 with a significance value of 0.004 (p <0.05).